Pengaruh Penyerapan Tenaga Kerja dalam Kemajuan Ekonomi Kreatif - Risdiandari, Nasya Ivana; Nisa, Fauzatul Laily (Jurnal Ekonomika : INDEPENDEN, 2024)
Economic models based on manufacturing and natural resources are shifting toward creativity and innovation, and the creative economy is becoming a more important sector in global economic growth. The creative economy is primarily defined by creativity, concept, passion, and individual achievement. The creative economy has the potential to convert society into human capital. This is greatly appreciated because it allows those who lost in the competition to improve their lifestyle so that they can compete again. The aim of this article is to identify the elements that influence labor absorption and to enhance our comprehension of the effects of labor absorption on the advance of the creative economy. The research findings indicate that employment opportunities, income levels, intellectual property development exports, and cultural conservation all experience an increase within the creative economy sector. The appeal of this sector to employees plays a pivotal part in propelling the progess of the innovative economy.